Follicular Helper T Cells Are Major Human Immunodeficiency Virus-2 Reservoirs and Support Productive Infection. (26th August 2019) - Godinho-Santos, Ana; Foxall, Russell B; Antão, Ana V; Tavares, Bárbara; Ferreira, Tiago; Serra-Caetano, Ana; Matoso, Paula; Sousa, Ana E
Abstract: Follicular helper T cells (Tfh), CD4 lymphocytes critical for efficient antibody responses, have been shown to be key human immunodeficiency virus (HIV)-1 reservoirs. Human immunodeficiency virus-2 infection represents a unique naturally occurring model for investigating Tfh role in HIV/acquired immune deficiency syndrome, given its slow rate of CD4 decline, low to undetectable viremia, and high neutralizing antibody titers throughout the disease course. In this study, we investigated, for the first time, Tfh susceptibility to HIV-2 infection by combining in vitro infection of tonsillar Tfh with the ex vivo study of circulating Tfh from HIV-2-infected patients. We reveal that Tfh support productive HIV-2 infection and are preferential viral targets in HIV-2-infected individuals. Abstract : Follicular helper T cells support productive HIV-2 infection and are preferential viral targets in HIV-2-infected individuals. This is particularly relevant given the slow rate of CD4 decline, reduced viremia, and high titers of neutralizing antibodies that characterize HIV-2-infected patients.